Determinants of Money Demand in ASEAN-4 Countries - Eileen, Teo Mei Ting (Universiti Malaysia Sarawak (UNIMAS), 2022)
Money demand is important in formulating the monetary policy. Therefore, this study aims to identify the determinants of money demand in ASEAN-4 countries of Malaysia, Thailand, Singapore and Philippines. Panel unit root tests, panel cointegration test, Pooled Mean Group (PMG), Fully Modified Ordinary Least Squares (FMOLS) estimators, and pairwise Dumitrescu Hurlin panel causality test have been employed in this study. The determinants of money demand chosen are the real gross domestic product, interest rate, and inflation rate in this study. The data employed over the period from 1990 to 2020. Moreover, the empirical findings indicate that all variables are significant in affecting money demand in long run, with real gross domestic product positively affecting money demand but interest rate and inflation rate negatively affecting money demand. However, interest rate shows insignificant short run influence on money demand in ASEAN-4 countries. In short run, real gross domestic product has significant negative influence on money demand, but inflation rate has significant positive influence on money demand. Furthermore, short run causal relationships have been found between the variables in ASEAN-4 countries. Thus, some recommendations are listed in this study to ensure the sustainable growth of money demand.